Intervensi Cognitive Behaviour Therapy dalam Mengatasi Perilaku Maladaptif: Program PKBI di PSBR Taruna Jaya 1 - Dian Fitriani; Debi Primanda (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Maladaptive behavior has implications for the mental and emotional well-being of adolescents. This behavior risks hindering the formation of healthy social relationships, and interferes with their academic and social development. Cognitive Behaviour Therapy (CBT) is a therapeutic approach that focuses on the relationship between one's thoughts, feelings, and behavior. In this study, researchers used a learning approach through learning theory in implementing CBT to overcome maladaptive behavior at the Taruna Jaya 1 Youth Development Institution. This study used a descriptive research method. This study explains the maladaptive behavior of 1 child at the Bina Adolescent Social Institution Taruna Jaya 1 by conducting an intervention in the form of a reflection of the cognitive behavioral therapy method. The results of this study show that the integration of learning approaches and psychosocial therapy in CBT can be effective in overcoming maladaptive behavior in adolescents in social institutions through BENI's English Character Learning program.